The effect of Torreya grandis inter-cropping with Polygonatum sibiricum on soil microbial community - Wang, Quanchao; Peng, Xiaojie; Yuan, Yuxuan; Zhou, Xudong; Huang, Jianqin; Wang, Haonan (Frontiers in Microbiology, 2024)
BackgroundInter-cropping is a reasonable planting pattern between different plants. Inter-cropping of Torreya grandis with Polygonatum sibiricum is a relatively mature planting pattern in China, which has been applied to improve soil ecological environment and reduce the occurrence of pests and diseases in China. However, there is currently limited knowledge on the response of soil microbial communities to this practice.MethodsIn this study, we employed Illumina MiSeq sequencing coupled with Functional Annotation of Prokaryotic Taxa (FAPROTAX) and Fungi Functional Guild (FUNGuild) analyses to investigate the dynamic changes in soil microbial communities across seven treated groups [the bulk soil of the T. grandis inter-cropping with P. sibiricum (IB), the bulk soil for mono-cropping of P. sibiricum (PB), the bulk soil for mono-cropping of T. grandis (TB), the P. grandis rhizosphere soil of the T. grandis inter-cropping with P. sibiricum (IPR), the rhizosphere soil for mono-cropping of P. sibiricum (PR), the T. grandis rhizosphere soil of the T. grandis inter-cropping with P. sibiricum (ITR), and the rhizosphere soil for mono-cropping of T. grandis (TR)].ResultsThe results showed that the rhizosphere soil of Torreya-Polygonatum inter-cropping exhibited higher microbial community richness, diversity and evenness than mono-cropping (ITR > TR, IPR > PR). Inter-cropping increased the abundance of Micrococcaceae, Xanthobacteraceae, Saitozyma, while decreased Bacillus, Burkholderia, Streptomyces, Cladosporium, and Gibberella significantly of the rhizosphere soil of T. grandis. Further, the abundance of pathogens, such as Fusarium and Neocosmospora, was higher in mono-cropping samples compared to inter-cropping. There existed distinct variations in bacterial and fungal communities among all groups except for IB and TB. The FAPROTAX and FUNGuild analyses results indicated that inter-cropping significantly enhanced soil microbial function associated with nutrient cycling and exhibited a consistent increase in the relative abundance of nitrogen-cycling and carbon-cycling bacteria, and decreased the abundance of plant pathogen guild in the inter-cropping sample ITR compared to the mono-cropping TR.ConclusionOur findings suggest that T. grandis inter-cropping with P. sibiricum not only enhance the diversity of soil microbial communities, but also improve the nitrogen and carbon cycling functions. In addition, the inter-cropping can effectively reduce the relative abundance of some soil-borne pathogens for T. grandis and P. sibiricum, indicating that this intercropping method may alleviate the impact of pathogens on crops, thus providing assistance for plant disease prevention and sustainable management.